The effect of entrepreneurial education on university student’s entrepreneurial self-efficacy and entrepreneurial intention - Dwi Atmono; Muhammad Rahmattullah; Ananda Setiawan; Rochman Hadi Mustofa; Diaz Aziz Pramudita; Titik Ulfatun; Reza Reza; Achmad Mustofa (International Journal of Evaluation and Research in Education (IJERE), 2023)
The purpose of this study is to find out the impact of curriculum attendance (CA) and extracurricular activities (EA) on entrepreneurial self-efficacy (ESE) and entrepreneurial intentions (EI) in Indonesian students. This research is elaborated using the quantitative method with SEM-PLS to find out the studied phenomena. Decision questionnaires from questionnaires that have been used in previous studies. The questionnaire was responded to by 733 students who had studied entrepreneurship education during COVID-19 pandemic. The results showed that the presence of the curriculum attendance and extracurricular activities had a positive impact on entrepreneurial self-efficacy and entrepreneurial intentions. Extracurricular activities and entrepreneurial self-efficacy have a positive impact on entrepreneurial intentions. However, the presence of the curriculum has no impact on entrepreneurial intentions. This is the first step for universities and students to realize that the presence of the curriculum needs to be reconstructed in order to have an impact on entrepreneurial intentions.